Correlation between Hypokalaemia and Hypomagnesemia - Uddin, Md Sultan (Journal of Dhaka National Medical College & Hospital, 2015)
Introduction : Experimental and clinical observations indicate a close relationship between magnesium and potassium status of our body. Such study in our country is meagre which lead us to conduct this study. Methodology : This was a prospective study conducted in a tertiary care urban hospital in Dhaka City. 183 children were included randomly from either sex. Result : 71 Patients were hypokalaemic (38.8%) and the rest 112 (61.2%) were normokalaemic. Serum magnesium level was 2.004 mmol/L in hypokalaemic children whereas in normokalaemic children serum magnesium level was 2.17 mmol/L. A positive correlation was found between hypokalaemia and hypomagnesemia. J. Dhaka National Med. Coll. Hos. 2015; 21 (01): 17-18